Dissolved organic matter fluorescence at wavelength 275/342 nm as a key indicator for detection of point-source contamination in a large Chinese drinking water lake. (February 2016) - Zhou, Yongqiang; Jeppesen, Erik; Zhang, Yunlin; Shi, Kun; Liu, Xiaohan; Zhu, Guangwei
Abstract: Surface drinking water sources have been threatened globally and there have been few attempts to detect point-source contamination in these waters using chromophoric dissolved organic matter (CDOM) fluorescence. To determine the optimal wavelength derived from CDOM fluorescence as an indicator of point-source contamination in drinking waters, a combination of field campaigns in Lake Qiandao and a laboratory wastewater addition experiment was used. Parallel factor (PARAFAC) analysis identified six components, including three humic-like, two tryptophan-like, and one tyrosine-like component. All metrics showed strong correlation with wastewater addition ( r 2 > 0.90, p < 0.0001). Both the field campaigns and the laboratory contamination experiment revealed that CDOM fluorescence at 275/342 nm was the most responsive wavelength to the point-source contamination in the lake. Our results suggest that pollutants in Lake Qiandao had the highest concentrations in the river mouths of upstream inflow tributaries and the single wavelength at 275/342 nm may be adapted for online or in situ fluorescence measurements as an early warning of contamination events. This study demonstrates the potential utility of CDOM fluorescence to monitor water quality in surface drinking water sources. Graphical abstract: Highlights: PARAFAC modeling decomposed CDOM fluorescence into six components. Sewage additions correlated strongly with all fluorescent components. Potential point-source contamination occurs in the upstream river mouths. 275/342 nm is the most responsive wavelength to the sewage concentrations.